ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND INTENTION TO QUIT: MEDIATING ROLE OF JOB BURNOUT AMONG CALL CENTER AGENTS IN METRO MANILA, PHILIPPINES - Tocle, Redmund Joseph (Social Sciences and Development Review, 2025)
This research aimed to investigate the relationship between organizational citizenship behavior (OCB) and turnover intention, with the mediation of job burnout among call center agents in Metro Manila. A total of 175 participants were recruited through snowball sampling and responded to an online survey. Descriptive statistics were used to determine the average levels of OCB, job burnout, and turnover intention among respondents. Spearman correlation analysis was performed to examine the relationships between these variables, while mediation analysis using the Med-Mod module in JAMOVI assessed the mediating role of job burnout. Results revealed that job burnout fully mediates the relationship between OCB and turnover intention. These findings highlight the importance of promoting organizational citizenship behavior to mitigate turnover intention by addressing job burnout.
Keywords: Organization; Citizenship; Behavior; Burnout; Turnover